Introduction to Fluorescence Sensing - Demchenko, Alexander P. (Springer Netherlands : Imprint: Springer, 2009)
Fluorescence sensing is a rapidly developing field of research and technology. Its target is nearly the whole world of natural and synthetic compounds being detected in different media including living bodies. The application area range from control of industrial processes to environment monitoring and clinical diagnostics. Among different detection methods fluorescence techniques are distinguished by ultimate sensitivity, high temporal and spatial resolution and versatility that allows not only remote detection of different targets but their imaging within the living cells. The basic mechanism of sensing is the transmission of the signal produced by molecular interaction with the target to fluorescent molecules, nanoparticles and nanocomposites with the detection by devices based on modern electronics and optics. In this interdisciplinary field of research and development the book is primarily intended to be a guide for students and young researchers. It is also addressed to professionals involved in active research and product development serving as a reference for the recent achievements. The users of these products will find description of principles that could allow proper selection of sensors for particular needs. Making a strong link between education, research and product development, this book discusses future directions.